Integration aspects of subsequent EU joiners - Cicero I. Limberea; Mihaela Onofrei; Mihaela Tofan (IBSU Scientific Journal (IBSUSJ), 2009)
This article aims to analyze the economic policy aspects of the European Union adherence requirements within the specific microeconomic framework of the postcommunist Eastern European countries during their transition to a free markets economic system. The authors observe that the framework for integration has not been separated between the member countries which had functioned as free market economies throughout the post World War II years that had initially formed the Union, and the newer entrants which were mostly still in a postcommunist transition on their adherence dates. They argue that the transition of the labor markets in such countries may require special attention as the free market mechanisms have not yet reached equilibrium levels and the degree of absorption for the labor force in those countries is still low compared to more mature market economies, thus central bank inflation targeting in these countries prior to the long term rate of unemployment reaching the natural rate is not the optimal solution.
Keywords: 330; EU accession; Maastricht; labor force absorption; migration; tax; uniform integration